2006
DOI: 10.1590/s1413-35552006000300010
|View full text |Cite
|
Sign up to set email alerts
|

Tradução e adaptação cultural do WORC: um questionário de qualidade de vida para alterações do manguito rotador

Abstract: Objetivo: Realizar a tradução e a adaptação cultural do questionário WORC (The Western Ontario Rotator Cuff Index) para a língua portuguesa para ulterior validação no Brasil. Métodos: O protocolo aplicado consistiu em: 1) Preparação, 2) Tradução, 3) Tradução de volta à língua original (retro-tradução), 4) Interrogatório Cognitivo e 5) Relato de Informações. Ao serem concluídas as etapas de tradução e retro-tradução, as versões foram enviadas para os autores do WORC original, que as aprovaram para continuação d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 16 publications
2
41
0
9
Order By: Relevance
“…In order to maintain the meaning of 'any rough play which overloads the shoulder and is not violent' , the question was translated as "playing, rolling on the floor". The same alteration was suggested for the translation of the same question in the WORC 12 . Some patients suggested alterations for question 6, in which the expression "enrijecimento" was changed to "enrijecimento/endurecimento".…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…In order to maintain the meaning of 'any rough play which overloads the shoulder and is not violent' , the question was translated as "playing, rolling on the floor". The same alteration was suggested for the translation of the same question in the WORC 12 . Some patients suggested alterations for question 6, in which the expression "enrijecimento" was changed to "enrijecimento/endurecimento".…”
Section: Discussionmentioning
confidence: 73%
“…All WOSI versions in other languages under development use this very protocol. In the WORC (Western Ontario Rotator Cuff Index) translation and cultural adaptation process to Portuguese, the same translation and cultural adaptation process was used 12 . Guillemin 8 proposes a standard procedure for translation and cultural adaptation of instruments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The translations should be mainly evaluated in terms of conceptual equivalence so that necessary grammatical changes can be conceptually similar to another culture. With regard to the cross-cultural adaptation, cultural factors such as habits and activities of a population should be considered because an activity which is not common in a certain population can make the instrument's adaptation invalid 22,23 . In the present study, no impediments were found either in the Brazilian Portuguese language or in the cultural aspects which could render unviable Table 4.…”
Section: Development Of the Adlq-translated Version And Cross-culturamentioning
confidence: 99%